2018
DOI: 10.5217/ir.2018.16.3.416
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and risk factors of venous thromboembolism in Japanese inpatients with inflammatory bowel disease: a retrospective cohort study

Abstract: Background/AimsVenous thromboembolism (VTE) is a major extraintestinal manifestation in inflammatory bowel disease (IBD), regarded as an independent risk factor for VTE according to reports from Western countries. However, the incidence and risk factors of VTE in Asian IBD patients are not fully understood. We aimed to reveal the incidence and risk factors of VTE in Japanese IBD inpatients.MethodsThe incidence of VTE in inpatients with IBD (n=340), gastrointestinal cancers (n=557), and other gastrointestinal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 23 publications
1
29
3
1
Order By: Relevance
“…Abbreviation: VTE, venous thromboembolism. about the same as that in inpatients with inflammatory bowel disease, which has been reported at 5.3%, 22 and low compared to that in in-patients with advanced cancer or acute ischemic stroke, reported at 33.7% and 40.2%, respectively. 13,16 Inpatients with depression may thus have a lower prevalence of asymptomatic VTE than patients hospitalized for physical illness.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Abbreviation: VTE, venous thromboembolism. about the same as that in inpatients with inflammatory bowel disease, which has been reported at 5.3%, 22 and low compared to that in in-patients with advanced cancer or acute ischemic stroke, reported at 33.7% and 40.2%, respectively. 13,16 Inpatients with depression may thus have a lower prevalence of asymptomatic VTE than patients hospitalized for physical illness.…”
Section: Discussionmentioning
confidence: 59%
“…3,4 Studies that examined VTE in patients hospitalized at other departments reported 71.4-100% of cases to be asymptomatic. 14,15,17,[19][20][21][22]24,25 Asymptomatic VTE thus seems to be common in psychiatric as well as nonpsychiatric inpatients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, more than 50% of the reported thrombotic events were asymptomatic. 21,22 Therefore, proactive screening could be useful for early identification of thrombosis; this is especially important for thrombosis with atypical presentation such as intra-abdominal thrombosis. In our study, more patients developed intra-abdominal venous thrombosis than PE, and the reported symptoms were mostly nonspecific such as abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Известно, что воспаление при ЯК приводит к изменениям в системе гемостаза: увеличению прокоагулянтных факторов и снижению фибринолитической активности, что при наличии генетической предрасположенности способствует манифестации тромбофилии [3,6,7]. Частота встречаемости тромбоза периферических вен и тром-Thrombophilia in a Patient with Ulcerative Colitis Тромбофилия у пациента с язвенным колитом боэмболии легочной артерии у больных ЯК больше в три раза по сравнению со здоровым населением, а при наличии у этих пациентов наследственных факторов риска, например, мутации фактора V Лейдена, риск тромботических событий возрастает в пять раз [3,8,9]. Описаний случаев тромбообразования в полости ПЖ при ЯК в имеющейся литературе нам найти не удалось.…”
Section: Discussionunclassified